Ali Mustafa Yaqub's Criticism Method of Hadith in Determining Islamic Law: Analysis of Performing Hajj with Unlawfully Obtained Wealth - Dadah, Dadah; Rahmah, Siti; Fatia, Azharia; Chalida, Sri; Aniqa, Sania (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2023)
This study aims to examine Ali Mustafa Yaqub's approach to critiquing hadith in the formation of Islamic jurisprudence, particularly focusing on the modern issue of performing hajj with unlawfully gained wealth. Employing a qualitative methodology, the research utilizes Yaqub's hadith criticism framework to explore this issue. Findings from the discourse and analysis illustrate that Yaqub's method offers profound insights into the complexity of Islamic legal matters, particularly concerning Hajj with unlawful fund, by underscoring the significance of sanad quality and its legal implications. The study concludes that Yaqub's analytical methodology in examining the legality of Hajj with unlawful wealth comprises three primary elements: sanad as well as matan critique, and hadith interpretation. In critiquing the sanad, Yaqub not only relies on personal judgment but also consults experts in hadith studies and authoritative texts. Additionally, he conducts comparisons of scholars' opinions to evaluate narrator reliability. In matan critique, he not only considers linguistic conformity and Quranic alignment but also conducts editorial analysis and contextualizes it. Moreover, in interpreting the hadith, he demonstrates a deep understanding of the prohibition of using unlawfully obtained funds for performing Hajj, despite the hadith's weak classification. Yaqub effectively presents his argument against using prohibited funds for Hajj within Islamic principles. Furthermore, the research underscores the importance of a comprehensive approach in addressing contemporary challenges in Islamic law.